Phytochemical Composition, GC-MS Profiling, Antibacterial and Antioxidant Activities of Tarenna asiatica Stem Extracts (International Journal of Pharmaceutical Sciences and Drug Research, 2026)
Tarenna asiatica is widely used in traditional medicine to treat a range of skin diseases. The current study focused on the stem extracts of the plant to evaluate its phytochemical composition, gas chromatography-mass spectroscopy (GC-MS) profile, and antibacterial and antioxidant efficacy. Alkaloids, flavonoids, steroids, terpenoids, and phenols were detected by qualitative phytochemical screening. The ethanol and chloroform extracts showed the highest phenol and flavonoid contents, respectively. The ethanol extract exhibited significant radical scavenging ability in the DPPH assay and reducing power assay. Antibacterial activity was assessed using the well diffusion method. The chloroform extract demonstrated significant antibacterial activity, exhibiting the highest zone of inhibition against Escherichia coli (17.67 ± 0.33 mm), while the methanolic extract indicated no activity. The chloroform extract had the lowest minimum inhibitory concentration (MIC) value against E. coli, Bacillus subtilis, and Staphylococcus aureus, measuring a value of 0.156 mg/mL. In thin-layer chromatography (TLC) bioautography, inhibition zones for all tested pathogens were observed at Rf values of 0.16 and 0.37. GC-MS analysis revealed the presence of retusine and salvigenin as the chief flavonoid compounds in the chloroform extract. The results of the present study highlight the potential value of T. asiatica stem extracts as a source of antibacterial agents, especially the chloroform extract.